Monolithic integration of GaAs/A1GaAS photonic devices using quantum well intermixing - Chan, Yuen Chuen (2008)
In this project, a novel QWI technique, based on the impurity free vacancies induced disordering (IFVD) technique, has been developed. This technique uses undoped and Er-doped sol-get SiO2 to achieve selective intermixing across a GaAs/AiGaAs laser structure.